Ricciocarpos natans (Marchantiophyta, Ricciaceae), new to Costa Rica, with a survey of its presence in Latin America - Acuña Castillo, Rafael (2023)
Background and Aims: Ricciocarpos natans is one of the few species of truly aquatic hepatics. It has a subcosmopolitan distribution and appears to be more common in temperate areas. The species has been considered to be very rare in Central America where it was known only from Panama. The objective of this study is to report the presence of this species in Costa Rica and to survey its current distribution in Latin America. Methods: We provide an overview of the distribution of the floating aquatic liverwort Ricciocarpos natans in Latin America based on literature, herbarium specimens and unequivocal photographic records across the region, as well as field work in Costa Rica. Key results: Ricciocarpos natans is reported as new for Costa Rica. We provide the most complete survey to date of the geographic distribution of the species in Latin America. Conclusions: Our survey shows that Ricciocarpos natans appears to be more common and widely distributed in the Neotropics than previously assumed. Its assumed rarity seems to be the result of insufficient collection efforts.